Writing in sociology - Edwards, Mark Evan (Los Angeles : SAGE, 2015)
With humor and empathy, Mark Edwards's handbook provides undergraduate and early-career graduate students guidance in sociological writing of all kinds. Writing in Sociology offers unusual approaches to developing ideas into research questions, utilizing research literature, constructing research papers, and completing different kinds of course writing (including case studies, theory papers, and applied social science projects). New chapters in the Second Edition offer insights into giving and receiving effective peer review and presenting qualitative research results. By focusing on how to think about the goals and strategies implicit in each section of a writing project this book provides accessible advice to novice sociological writers.
Includes bibliographical references and index.
Description based on MARC record for print version.
Keywords: Sociology -- Authorship; Sociology -- Research; Report writing; Sociology -- Study and teaching (Higher).